2008
DOI: 10.1002/dir.20110
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious processing of Web advertising: Effects on implicit memory, attitude toward the brand, and consideration set

Abstract: Consumers have become increasingly savvy about technology in recent years, and many of them ignore Web ads during online activities. In this context, measuring advertising effects based on the traditional cognitive models of information processing may undervalue the effectiveness of Web ads. This study experimentally examined the effects of unconscious processing of Web ads by manipulating the level of attention paid to the ad (directed vs. non-directed attention). Online advertisers should be encouraged by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 40 publications
5
68
0
2
Order By: Relevance
“…Burgess (2015) found internet motives signifi cant predictors of user response to online banner ads such as to notice, ignore or click on them. Internet motives expose users to online ads which in turn induce their direct response to online advertising (Yoo, 2008). According to Chatterjee (2008) direct response to online ad exposure is click on ads.…”
Section: Proposed Model and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Burgess (2015) found internet motives signifi cant predictors of user response to online banner ads such as to notice, ignore or click on them. Internet motives expose users to online ads which in turn induce their direct response to online advertising (Yoo, 2008). According to Chatterjee (2008) direct response to online ad exposure is click on ads.…”
Section: Proposed Model and Hypothesesmentioning
confidence: 99%
“…Frequency of visiting the web and amount of time spend on web per visit infl uence the online advertising effectiveness (Mohammed & Alkubise, 2012). For instance, several studies such as Fang, Singh, and Ahluwalia (2007), Yoo (2008) and Lee and Cho (2010) found that frequency of visiting the web and time spent on web expose the users to web ads which in response infl uence their attitudes and behavior toward web advertising. Frequency of exposure is an infl uential psychological cue which affects consumers' memory, attitudes and behaviors (Lee & Cho, 2010).…”
Section: H1 the Causal Relationship Between Snss Entertainment Motivmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising as a well-crafted ad is an important success-determinant from an advertiser's perspective [7] to reach the target audience and convince potential buyers to click the ad. Current research has investigated either the use of individual textual elements (e.g., [8]) or message framing (e.g., [9]). Information cues, which marketers commonly use to influence customer behavior by providing additional information, have received a lot of scholarly attention in the field of traditional marketing [1].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a review of the literature verified that a large portion of emotional advertising is dedicated to traditional media, such as print and television advertisements (Royo & Gutierrez, 2000;Heath & Nairn, 2005;Lin, 2011). Very few studies have focused on online advertising, as most only investigated the effective use of banner advertisements (Yoo, 2008;Porta et al, 2013;Noble et al, 2014) and pop-up advertisements (Nysveen & Breivik, 2005;Qin et al, 2011). The effectiveness of e-commerce advertisements using emotional and rational appeals, particularly in the context of video advertising, is unclear and at best contradictory.…”
Section: Introductionmentioning
confidence: 99%